ANALISIS KINERJA SOSIAL DAN KINERJA KEUANGAN USAHA EKONOMI DESA-SIMPAN PINJAM (UED-SP) BINA SEJAHTERA DI DESA SIBABAT KECAMATAN SIBERIDAKABUPATEN INDRAGIRI HULU PROVINSI RIAU - Angga Kurniawan Rasmi; Ahmad Rifai; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aimsto analyze social performance and financial performance of Microfinance Institutions UED-SP Bina Sejahtera, inthe village of Sibabat, Indragiri Hulu. Social performancewas analyzed by using the MIX Market Social Performance Indicators, and financial performance was analyzed by using PEARLS based the financial data during 2010-2013 period. The results showed tha the MFIUED-SP Bina Sejahtera is not yet optimal in crease loan volume growth. Development of systems and strategies based on staff productivity indicators for the number of borrowers and loan volume and an increase inthe ratio of staff incentivesis not yet optimal also. Performance improvement of the borrower and the borrower poor people increased. Rangeof business sectorsare dominated by agriculture and trade, which is indicated by the lending volume indicator on agriculture and trade. The financial performance of MFIs UED-SP obtained undersome indicators in ideal conditions, that are: the ratio ofcurrent assets, the ratio ofexternal loans, institutional capital ratio, the ratio of non perfoaming loans, the ratio of non-productive assets, the ratio of loan income, asset growth, and the growth of savings shares. Financial performance indicators have not been achieved are the ratio of the Loan Losses Allowances for Delinquent >12 Month ratio, Net Loan Loss Allowances for Delinquent 1-12 Month ratio, Net Loans Ratio, Member Share Capital Ratio , Operating Expenses Ratio, Net Income Ratio, Non-earning Liquid Assets Ratio, Net Loans growth Ratio, Institutional Capital Growth Ratio.   Keywords: Microfinance Institution (UED-SP), protection, non perfoaming loan